A mixed methods analysis of experiences and expectations among early‐career medical oncologists in Australia. Issue 5 (26th January 2018) - Wong, W. K. Tim; Kirby, Emma; Broom, Alex; Sibbritt, David; Francis, Kay; Karapetis, Christos S.; Karikios, Deme; Harrup, Rosemary; Lwin, Zarnie
Abstract: Aim: A viable and sustainable medical oncology profession is integral for meeting the increasing demand for quality cancer care. The aim of this study was to explore the workforce‐related experiences, perceptions and career expectations of early‐career medical oncologists in Australia. Methods: A mixed‐methods design, including a survey ( n = 170) and nested qualitative semistructured interviews ( n = 14) with early‐career medical oncologists. Recruitment was through the Medical Oncology Group of Australia. Qualitative data were thematically analyzed and for the survey results, logistic regression modeling was conducted. Results: Early‐career medical oncologists experienced uncertainty regarding their future employment opportunities. The competitive job market has made them cautious about securing a preferred job leading to a perceived need to improve their qualifications through higher degree training and research activities. The following themes and trends were identified from the qualitative and quantitative analyses: age, career stage and associated early‐career uncertainty; locale, professional competition and training preferences; participation in research and evolving professional expectations; and workload and career development opportunities as linked to career uncertainty. Conclusion: Perceived diminished employment opportunities in the medical oncology profession, and shifting expectations to be "more qualified, " have increased uncertainty among junior medical oncologists in terms of their future career prospects. Structural factors relating to adequate funding of medical oncology positions may facilitate or inhibit progressive change in the workforce and its sustainability. Workforce planning and strategies informed by findings from this study will be necessary in ensuring that both the needs of cancer patients and of medical oncologists are met.